Vier neue Texteditionen des Göttinger Septuaginta-Unternehmens - Dochhorn, Jan (Theologische Rundschau, 2023)
In the last decade, four books of the Septuagint have been published in the renowned Göttinger Septuagint edition. The editions differ in their editorial task since the transmission of the books of the Septuagint is all but the same throughout. The editions also differ in their method - which probably indicates that promising innovations are on the way in the editorial practice of the Septuaginta-Unternehmen (which - in a new institutional setting and mainly coordinated by Felix Albrecht - still exists). The present review aims to advertise the work of the Septuaginta-Unternehmen, indicating that it is highly exciting what is (to be) done there and, in addition, that textual criticism is more than collating and collecting data but both a geisteswissenschaft and also a phenomenon of human geist. Apart from that, this review brings some principal considerations (but not extensively unfolded) to the fore: 1. In the apparatus, Greek should be written with diacritics (breaths, accents). The apparatus does not note what the manuscripts read but what they attest - and they attest Greek words/phrases which, of course, have diacritics. 2. Names borrowed from Hebrew should also be written with diacritics - and according to the Greek tradition. The practice of giving them a Masoretic flavor that still is predominant in Biblical philology deserves to be abandoned (before the 19th century, there most probably never existed a Εὕα in Greek; Eve is Εὔα). 3. Some reorganization could make the apparatus more accessible. To exclude misunderstanding I add: The wealth of information provided by the apparatus is not a problem but a benefit.FELIX ALBRECHT (Ed.), Psalmi Slomonis (Septuaginta. Vetus Testamentum Graecum Auctoritate Academiae Scientiarum Gottingensis Editum XII,3). Göttingen: Vandenhoeck & Ruprecht 2018 - PETER JOHN GENTRY (Ed.), Ecclesiastes (Septuaginta. Vetus Testamentum Graecum Auctoritate Academiae Scientiarum Gottingensis Editum XI,3). Göttingen: Vandenhoeck & Ruprecht 2019. - ROBERT HANHART (Ed.), Paralipomenon Liber II (Septuaginta. Vetus Testamentum Graecum Auctoritate Academiae Scientiarum Gottingensis Editum VII,2). Göttingen: Vandenhoeck & Ruprecht 2014 - UDO QUAST (Ed.), Ruth (Septuaginta. Vetus Testamentum Graecum Auctoritate Academiae Scientiarum Gottingensis Editum IV,3). Göttingen: Vandenhoeck & Ruprecht 2006 (2009).